Focus groups strategy and its impact on the achievement of primary school students in art education (Al-Academy, 2023)
Art education is one among the fundamental subjects for elementary school students, because it contributes to assembling learners’ personalities and developing their technical skills. For this reason, this research comes, which aims to understand the effect of the task groups’ strategy in developing the performance of elementary school students in art education. to realize the goal of the research, the researcher put the subsequent hypotheses:-There is not any statistically significant difference at the amount (5%) between the typical many students between the experimental group that studied consistent with the strategy of task groups and therefore the control group that studied in keeping with the same old method that they obtained per the appliance of the observation form afterwards, and to verify the validity of the hypothesis, the researcher applied his experience On the 2 groups and using the achievement test (T-test), it had been concluded that the experimental group that studied with the task strategy excelled in its skill performance in step with the observation form prepared by the researcher, that the researcher recommends using the task strategy for its impact on developing technical skills